Posthumanism is Right in so far as Humanism is Not Human Enough: Introducing Vol. 11 No. 2 - Min Seong Kim (Retorik: Jurnal Ilmu Humaniora, 2023)
Alongside the “Anthropocene,” “posthuman” undoubtedly counts among the most prominent keywords of today’s academic discourses. Its increasing prominence in the Indonesian academia was reflected in the theme of the Sanata Dharma Berbagi conference held in October 2023. The title of the fifth edition of the ASLE-ASEAN Ecocritical Conference held in Chiang Rai, Thailand, just a month later, too, was “Posthuman Southeast Asia.” If the conference series had understandably close affinity with broadly posthumanist orientations from its inception, the title of the fifth iteration of the conference perhaps distinguished itself with its constative resonance, that Southeast Asia already is posthuman. The avenues for thought that the posthumanist wave clears, particularly in the Indonesian context wherein it represents advances beyond a myopic culturalism that so often constrains research in the humanities, deserve full intellectual attention from those in the field of cultural studies in the country. However, even though I myself have recently defended certain theoretical projects that are sometimes associated with posthumanism, I still remain hesitant to ride the wave of posthumanism at full speed. For I have also found myself wondering whether the great strides promised by posthumanism risk obfuscating alternative paths forward potentially opened by other lines of thought.